Implementation of the Scaffolding Method in Arabic Language Learning at Madrasah Tsanawiyah Darussalam Banjeng - Yuniarti, Lita; Hasanah, Uswatun; A’yun, Siska Qurrota; Azizaturrohmah, Wafiq; Azzahra, Talitha Rahma (Mantiqu Tayr: Journal of Arabic Language, 2026)
Arabic language learning at the Madrasah Tsanawiyah level continues to face challenges related to the gap between expected language competence and students’ actual abilities. The structural complexity of Arabic, combined with the use of less adaptive instructional methods, often results in low student participation and limited learning autonomy. This study aims to analyze the implementation of the scaffolding method in Arabic language learning at Madrasah Tsanawiyah Darussalam Banjeng and to examine its implications for students’ learning processes and outcomes. A descriptive qualitative approach was employed, with data collected through classroom observations, interviews, and documentation. The data were analyzed inductively through the stages of data reduction, data display, and conclusion drawing. The findings indicate that scaffolding provides systematic and gradual instructional support, enhances students’ mastery of vocabulary and sentence structures, and improves productive language skills, particularly speaking and writing. Moreover, the method fosters more collaborative classroom interactions and strengthens students’ learning independence. This study concludes that scaffolding is an effective pedagogical approach for Arabic language learning and holds significant potential for broader application in foreign language instruction within the madrasah context.